Comparison between Airborne LiDAR Data and Digital Image Matching for Surface Reconstruction - Carrilho, A. C. [UNESP]; Dos Santos, R. C. [UNESP]; Pessoa, G. G. [UNESP]; Galo, M. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2020)
Nowadays some aerial surveying projects (both manned or not) might integrate imagery and ranging sensor technology, thus allowing both the reconstruction of the surface from airborne laser scanning (ALS) and from the Photogrammetric pipeline through digital image matching (DIM). DIM algorithms have been continuously improved, therefore comparisons to other techniques such as ALS must be conducted. Despite the scientific community efforts, there are few evaluations regarding the extraction of building roofs using point clouds derived from both ALS and imagery. In this sense, this study provides a brief comparison between ALS and DIM point clouds and the accuracy that can be achieved in surface reconstruction and building roofs extraction. The experiments indicated that in some situations such as the building roof shape extraction, the accuracy is similar between these techniques, however, this is not valid for vertical accuracy, where larger differences were observed.
Keywords: Airborne Laser Scanning; Digital Image Matching; Point Cloud; Surface Reconstruction